GASTROINTESTINAL STROMAL TUMOURS ( GIST) - Baako, B. (My University, 2013)
GIST is the commonest mesenchymal neoplasm of the gastrointestinal tract. It was classified a leiomyoma, leiomyosarcoma until recently 1998 when it had been characterised by a specific histological and immunological pattern. GIST is proven only if the tyrosine kinase receptor kit- CD117 or the platelet derived growth factor receptor alpha (PDGFRA) can be demonstrated and spindle cell, epithelioid cells and cells of mixed differentiation are present histologically. It was unresponsive to chemo and radiotherapy until the Food and Drug Administration (FDA) of the USA’s approval of the tyrosine kinase inhibitor imatinib in the year 2000- the first effective systemic treatment to be discovered. Primary and secondary resistance can occur. Surgery in the early stages (<5cm), when it can be completely excised with healthy margins with no spillage or intraperitonea l bleeding has been curative.